Business for Society is Society's Business: Tension Management in a Migrant Integration Supply Chain. Issue 4 (8th November 2019) - Longoni, Annachiara; Luzzini, Davide; Pullman, Madeleine; Habiague, Martin
Abstract : Social enterprises are acquiring an increasingly relevant role as focal organizations for managing supply chains to address social problems. We argue that the presence of misaligned institutional logics between these focal organizations and their supply chain stakeholders generates tensions. Building on institutional theory and paradox theory, we analyzed seven dyadic relationships between a single focal social enterprise with a goal of migrant integration and its supply chain stakeholders. We propose relationship management mechanisms related to relationship governance, power, and trust to manage such tensions. We observe the application of different relationship management mechanisms relative to different types of tensions. Finally, we relate different relationship management mechanisms to specific tension management approaches referred to as complementarity, acceptance, and accommodation, and offer propositions based on our findings.